2010
DOI: 10.2478/s11532-010-0098-8
|View full text |Cite
|
Sign up to set email alerts
|

Composition-induced phase transition in a [Ag2HgI4:0.2AgI] mixed composite system doped with CuI

Abstract: Abstract:© Versita Sp. z o.o. A novel composite superionic system, [Ag 2 HgI 4 :0.2AgI]:xCuI, (x = 0.2, 0.4, 0.6 mol. wt.%), was prepared and [Ag 2 HgI 4 :0.2AgI] mixed system was used as the host. Electrical conductivity was measured to study the transition behavior at frequencies of 100 Hz, 120 Hz, 1 kHz, and 10 kHz in the temperature range 90° -170°C by a Gen Rad 1659 RLC Digibridge. Sharp increase in conductivity was observed for β-α phase transitions. As a result of increase in the dopant-to-host ratio, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
2
3
0
Order By: Relevance
“…wt% then increases in the temperature range from 150 C to 170 C. Variations in the composition of the dopant in the host affected the phase change within the temperature range from 150 C to 180 C. This phenomenon is usually observed in different composite system [10][11][12]. In the log T versus x plot (Figure 2(a) and (b)), this mixed composite system looks qualitatively similar to those reported in the literature [23] but the values differ quantitatively in different temperature range [15].…”
Section: Compositional Variation In Conductivitysupporting
confidence: 80%
“…wt% then increases in the temperature range from 150 C to 170 C. Variations in the composition of the dopant in the host affected the phase change within the temperature range from 150 C to 180 C. This phenomenon is usually observed in different composite system [10][11][12]. In the log T versus x plot (Figure 2(a) and (b)), this mixed composite system looks qualitatively similar to those reported in the literature [23] but the values differ quantitatively in different temperature range [15].…”
Section: Compositional Variation In Conductivitysupporting
confidence: 80%
“…In the log σT vs x plot (Fig. 2), this mixed composite system looks qualitatively similar to those reported in the literature [13] but the σ values differ quantitatively at different temperature range [19].…”
Section: Compositional Variation In Conductivitysupporting
confidence: 75%
“…AgI is known as typical superionic conductors, the superionic phase of AgI appears at 420 K. The value of the ionic conductivity is as high as about 1 Ω −1 cm −1 [14]. It has been observed that a much better solid electrolyte composite system can be prepared with the host [Cu 2 HgI 4 :0.2AgI] [13].…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations